PENGARUH PENDAPATAN DAN PERILAKU KEUANGAN TERHADAP MINAT MENABUNG (STUDI KASUS NASABAH PADA BANK BRI KCP TELUKDALAM KABUPATEN NIAS SELATAN - Sovia Trisnawati Saota (Universitas Nias Raya, 2023)
Destination study this is for knowing influence Income and Behavior Finance to Interest Save Customer at Bank BRI KCP Telukdalam Regency South Nias . Problem study this is part customer not enough have desire for saving , low behavior customer in arrange finance , as well as still many people who haven't realize importance management finance in _ life personal because Public still think save private bank only conducted by community that has income high . Type study is research that is quantitative. Subject in study this is customers of Bank BRI KCP Telukdalam Regency South Nias. Results study show Income and Behavior Finance have significant influence _ to Interest Save Customer at Bank BRI KCP Telukdalam Regency South Nias. Suggestions submitted researcher is for Keep going increase desire in save, so can used as fund backup in the future come and could have preparation when experience you difficulty cost not unexpected. Recommended to Bank BRI KCP Telukdalam customers in South Nias Regency so that they can arrange finance with income generated with keep money at the bank little by little so that deposited funds Becomes a lot , with keep money at the bank could guaranteed safe .